First Report of the Scandium Element in Pagrus pagrus Otoliths: A Potential Indicator of Thermal Activity From Gökçeada Island, Turkey - Bayram Kızılkaya; Hakan Ayyıldız; Aytaç Altın; Şükran Yalçın Özdilek (Acta Natura et Scientia)
In this study, surface morphology and chemical structure of Pagrus pagrus (Linnaeus 1758) sagittal otolith from the shores of Gizli liman to Kefalos Cape in the north of Gökçeada Island, Turkey were investigated using scanning electron microscopy (SEM) and energy dispersion X-ray spectroscopy (EDS) analyses. According to the results of SEM analysis, the species was found to be over two years old. The age rings of P. pagrus were clearly identified on the otolith by SEM. According to the EDS results, it was examined that the element contents of age rings and regions between the sagittal otoliths obtained by EDS analysis. It was observed that calcium, carbon, and oxygen elements that form the calcium carbonate were the highest in EDS analysis. In addition, it has been found that the percentage of protein in ring structures, especially, in rings related to the age factor showed an increase. It can be said that this structural difference plays a major role in the clarification of age ring. Furthermore, the scandium (Sc) element was firstly discovered in the structure of the sagittal otoliths of P. pagrus from Gökçeada, Turkey. Scandium is one of the indicator elements in thermal regions. This study describes the presence of scandium trace element for the first time in the structure of otolith.